Conhecimentos, atitudes e práticas de puérperas sobre a preparação do assoalho pélvico para o parto - Gondim, Edna Jéssica Lima (2019)
Objective: To evaluate knowledge, attitude and practice (KAP) of postpartum women about pelvic floor preparation for labor, as well as factors related to them. Method:An observational cross-sectional study, with a KAP questionnaire, was carried out at a public maternity clinic, between December 2017 and November 2018. Were included in the study postpartum women who underwent normal labor, who wanted a normal labor, and who were at least 14 years old. Data were collected through two forms: one for sociodemographic, clinical and obstetric data, and the other for KAP evaluation, consisting of 15 multiple-choice questions, out of which five evaluated knowledge, three, attitude, and seven, practice concerning pelvic floor preparation for labor. Results: 326 women took part in the research, with an average age of 24.3 years; 75.8% were in a stable relationship, 50.6% were multiparous, 60.4% had not planned the pregnancy, 66.3% had perineal tears and 3.7% underwent episiotomy. Concerning KAP, 2.5% showed satisfactory knowledge, 4.3% showed positive attitude, and 4.0% carried out pelvic floor preparation practices during pregnancy. We observed an association between education level and income with the knowledge aspect (p<0.05), and between education level and attitude (p<0.05). Conclusion: The KAP about pelvic floor preparation for labor were, generally, inadequate, corroborating the need for interventions in order to improve pelvic floor care during pregnancy.